EXPLORING THE IMPACT OF CUSTOMER EXPERIENCE AND PERCEIVED ENJOYMENT ON CUSTOMER LOYALTY: THE MEDIATING ROLE OF TRUST IN TIKTOKSHOP - Amelia, Emi; Hurriyati, Ratih; Sultan, Mokh. Adib; Kamaludin, Ahmad; Januar, Muhammad (Jurnal Riset Bisnis dan Manajemen, 2025)
Customer loyalty is crucial for a company's long-term success, particularly in competitive e-commerce. This study examines the impact of customer experience and perceived enjoyment on customer loyalty, with trust as a mediator, in the TikTok Shop context. Using a quantitative approach, data were collected from 150 TikTok Shop users who completed at least three transactions. SEM-PLS analysis shows that perceived enjoyment has a stronger direct effect on trust and loyalty than customer experience. The model explains 71.4% of trust variance and 62.1% of customer loyalty variance. The findings highlight the need for e-commerce businesses to enhance retention by ensuring seamless, enjoyable interactions and fostering trust through transparency, reliability, and engaging features. This study underscores the importance of integrating customer experience with trust-building strategies in social commerce.